All-solid-state lithium-sulfur battery composite positive electrode and preparation method thereof

By using small molecule sulfur in an all-solid lithium sulfur battery evenly dispersed with conductive agent and adding binder to enhance particle contact, the insulating characteristics and volume changes of sulfur cathode material are solved, and the rate performance and cycle stability of the battery are significantly improved.

CN119725369APending Publication Date: 2025-03-28YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA

Patent Information

Application Number
CN202411962207.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In all-solid lithium-sulfur batteries, the ion/electronic insulation characteristics of the sulfur positive electrode material limit the rate performance and charge and discharge efficiency of the battery. The sulfur redox reaction kinetics are slow, and the volume of the sulfur positive electrode changes greatly during the charge and discharge process, which may lead to the damage of the electrode structure and the decline in battery performance.

Method used

Small molecule sulfur is used as the active substance and the conductive agent to disperse evenly, and through improved preparation technology and mixing technology, the binder is added to enhance particle contact and form a composite positive electrode.

Benefits of technology

It improves the uniformity of lithium ion transmission, enhances the utilization rate of active substances, improves the cycle stability and electrochemical performance of the battery, and achieves higher discharge specific capacity and more stable cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725369A_ABST
    Figure CN119725369A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an all-solid-state lithium-sulfur battery composite positive electrode, which comprises the following steps: weighing raw materials of sodium thiosulfate, hydrochloric acid and a conductive agent (such as one or more of graphene, carbon nanotubes, conductive carbon black and acetylene black) according to a certain proportion, stirring, precipitating, washing and drying to obtain a sulfur-carbon precursor; and performing mechanical ball milling on the precursor and an electrolyte according to a certain proportion, and grinding with a binder to obtain a composite positive electrode, and taking the composite positive electrode as the positive electrode of the all-solid-state lithium-sulfur battery. According to the invention, the problem of non-uniform lithium ion transmission caused by large particle size of active substance sulfur is solved, so that the utilization rate of the active substance is improved; meanwhile, the problem of non-uniform dispersion of the active substance sulfur and the conductive agent carbon is solved, so that the cycle stability of the battery is improved; in addition, the addition of the binder enhances the contact of each component in the composite positive electrode, thereby obtaining more excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of all-solid-state lithium-sulfur batteries and relates to a composite positive electrode, in particular to an all-solid-state lithium-sulfur battery composite positive electrode, and a preparation method of the composite positive electrode. Background Art

[0002] With the growing global demand for clean energy and efficient energy storage solutions, all-solid-state lithium-sulfur batteries (ASSLSBs) have attracted much attention due to their unique advantages. This battery technology not only provides higher energy density than traditional liquid lithium-ion batteries, but also effectively solves the safety issues existing in liquid batteries. In all-solid-state lithium-sulfur batteries, the composite cathode is a key component, and its performance directly affects the electrochemical performance and cycle stability of the battery. By using solid-state electrolytes instead of traditional liquid electrolytes, all-solid-state lithium-sulfur batteries fundamentally eliminate the risks of electrolyte leakage and volatilization, greatly improving the safety performance of the battery. In addition, the use of solid-state electrolytes also simplifies the battery structure, saves space and weight, and thus increases the energy density of the battery. The design and optimization of composite cathode materials has become the key to achieving high-efficiency and long-life all-solid-state lithium-sulfur batteries.

[0003] Although the composite cathode of all-solid-state lithium-sulfur batteries (ASSLSBs) has great potential in achieving high energy density and safety, it still faces some challenges and problems in practical applications. First, the sulfur cathode material itself has the characteristics of ion / electronic insulation, which limits the battery's rate performance and charge-discharge efficiency; second, the sulfur redox reaction kinetics in all-solid-state lithium-sulfur batteries are slow, especially in the solid-solid conversion process between sulfur and lithium sulfide; in addition, the sulfur cathode undergoes large volume changes during charge and discharge, which may lead to damage to the electrode structure and degradation of battery performance. Therefore, optimizing the composite cathode of all-solid-state lithium-sulfur batteries is the key to their early commercialization and large-scale application.

[0004] To solve the above problems, researchers started from the following aspects. First, the particle size of sulfur should be reduced as much as possible and uniformly dispersed. For example, sulfur is uniformly deposited on carbon by vapor deposition (Publication No. CN111799459B) or liquid phase deposition (Journal of Colloid and Interface Science, 2021, Vol. 589, pp. 252-263), to obtain a sulfur composite positive electrode material with small sulfur particle size, large specific surface area, and uniform and close contact with the mixed powder, which improves the utilization rate of active substances in all-solid-state lithium-sulfur batteries and reduces the overall impedance and capacity loss of the battery, but the contact between the positive electrode components is still not close enough. Secondly, starting from the active substance, sulfur is replaced with sulfides that can alleviate volume expansion. For example, Li2S ("Electrochimica Acta", 2020, No. 358) and MoS2 ("Journal of Materials Chemistry A", 2015, Vol. 20, No. 3, pp. 10698-10702) synthesized in one step are used to replace sulfur, which is convenient and quick, and can be evenly mixed with a conductive agent, but the theoretical specific capacity of sulfide is not as high as that of sulfur. In addition, battery performance can be improved by starting with other components of the composite positive electrode, such as binders and additives. A patent application with publication number CN118867243A discloses a composite sulfur solid-state positive electrode material modified by LiNbO-3. The built-in electric field generated by the polarization of LiNbO-3 can slow down the degradation of the electrolyte in the positive electrode, while suppressing the formation of a space charge layer at the interface between the positive electrode and the solid electrolyte, so that the battery obtains a higher charge and discharge specific capacity and better cycle stability. Furthermore, adding high-entropy MXene to the above system provides a path for electrons inside the positive electrode, obtaining an all-solid-state lithium-sulfur battery with higher charge-discharge capacity and better cycle stability (publication number CN118867243A), but its sulfur utilization rate still needs to be improved. Summary of the Invention

[0005] The present invention aims to overcome the shortcomings of the prior art by providing a composite positive electrode for an all-solid-state lithium-sulfur battery and a method for preparing the composite positive electrode. The present invention utilizes small-molecule sulfur as the active material, which is uniformly dispersed with a conductive agent, providing a pathway for uniform and rapid lithium ion transport. This improves the active material utilization rate of the all-solid-state lithium-sulfur battery while achieving higher discharge specific capacity and more stable cycling performance.

[0006] The objective of the present invention is achieved through the following technical solution: an all-solid-state lithium-sulfur battery composite positive electrode, wherein the active material sulfur exists in the form of small molecules and is uniformly dispersed with a conductive agent, and contains a binder that enhances particle contact.

[0007] A method for preparing an all-solid-state lithium-sulfur battery composite positive electrode, for preparing the above-mentioned all-solid-state lithium-sulfur battery composite positive electrode, comprises the following steps:

[0008] S1. Add a conductive agent to water and stir and disperse the mixture to obtain solution A; add Na2S2O3·5H2O to solution A and stir, then slowly dropwise add hydrochloric acid and stir to obtain solution B; in solution B, the molar ratio of Na2S2O3·5H2O to hydrochloric acid is 1:2, and the molar ratio of the conductive agent to Na2S2O3·5H2O is 1:1-10;

[0009] S2, filtering and washing the solution B, and then drying the solution to obtain powder A;

[0010] S3, mixing powder A with the electrolyte and ball milling to obtain powder B;

[0011] S4. Powder B is mixed with a binder and ground manually to obtain a composite positive electrode.

[0012] The conductive agent in S1 is one or more of graphene, carbon nanotubes, conductive carbon black, acetylene black and Ketjen black.

[0013] The three stirring times in S1 are 0.5-2 h, 1-2 h and 6-12 h respectively.

[0014] In S2, suction filtration and cleaning need to be performed 3-10 times, the drying temperature is (50±5)° C., and the drying time is 6-36 hours.

[0015] The electrolyte in S3 is Li7P3S 11 、Li3PS4、Li 10 GeP2S 12 , Li6PS5Cl; the amount of electrolyte added is 40%-60% of powder B.

[0016] In the above-mentioned S3, the ball-to-material ratio of the mixed ball milling is 50:1-30, the ball milling speed is 200-600 rpm / min, and the ball milling time is 1-24 hours.

[0017] The binder in S4 is polytetrafluoroethylene or polyvinylidene fluoride, and the addition ratio of the binder is 1%-20% of the composite positive electrode.

[0018] The manual grinding time in S4 was 5-15 mins.

[0019] Both S3 and S4 were operated under high-purity argon atmosphere.

[0020] The present invention achieves the following beneficial effects: through innovative approaches, it addresses several key issues with cathode materials in all-solid-state lithium-sulfur batteries, significantly improving battery performance. First, the uneven lithium ion transport problem caused by the large particle size of the active sulfur material is effectively addressed. By preparing nano-sulfur and modifying its dispersion, uniform lithium ion transport is achieved, thereby improving the utilization rate of the active material. Second, the present invention addresses the uneven dispersion of the active sulfur material and the conductive carbon. Through improved preparation and mixing techniques, a uniform mixing of sulfur and carbon is achieved, thereby improving the battery's cycling stability, potentially exceeding the target of less than 5% capacity loss after 100 cycles. Finally, the addition of a binder significantly enhances the contact between the various components of the composite cathode, including the interaction between the active material, conductive agent, and binder. This enhanced contact improves the transport pathways for electrons and ions, resulting in superior electrochemical performance, enabling the battery to achieve a high specific capacity of 1000+ mAh / g, approaching the theoretical capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Graph showing the cycle performance of Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below with reference to the accompanying drawings.

[0023] The all-solid-state lithium-sulfur battery composite positive electrode has the active material sulfur in the form of small molecules, which is evenly dispersed with the conductive agent and contains a binder to enhance particle contact.

[0024] The present invention utilizes a precipitation method to obtain nanoscale sulfur, which is then mixed with a conductive agent via a solution dispersion method. A binder is then added and ball-milled to produce a composite positive electrode. This approach addresses the issues of uneven lithium ion transport caused by the large particle size of the active sulfur material, uneven dispersion of the active sulfur material and the conductive carbon agent, and loose contact between the components of the composite positive electrode, thereby improving active material utilization and electrochemical performance. The technical solutions of the present invention are further illustrated below with reference to specific examples.

[0025] Example 1

[0026] A method for preparing a composite positive electrode for an all-solid-state lithium-sulfur battery comprises the following steps:

[0027] S1. Add graphene to water and stir and disperse for 0.5 h to obtain solution A; add sodium thiosulfate (Na2S2O3·5H2O) to solution A and stir for 1 h, then slowly add hydrochloric acid (HCl) dropwise and stir for 6 h to obtain solution B; in solution B, the molar ratio of Na2S2O3·5H2O to HCl is 1:2, and the molar ratio of the conductive agent to Na2S2O3·5H2O is 1:1;

[0028] S2. After filtering and washing solution B six times, drying at 55° C. for 12 h to obtain powder A;

[0029] S3, 30% powder A and 60% electrolyte Li 10 GeP2S 12 , with a ball-to-material ratio of 50:1 and a rotation speed of 600 rpm / min, the mixed ball mill was used for 10 h to obtain powder B;

[0030] S4. Powder B was mixed with 10% binder PTFE (polytetrafluoroethylene) and ground manually for 5 minutes to obtain a composite positive electrode.

[0031] In the above-mentioned method for preparing the composite positive electrode, steps S3 and S4 are both performed under a high-purity argon atmosphere.

[0032] The all-solid-state lithium-sulfur battery assembled with the composite positive electrode was then taken out, placed at 25°C, and left to stand for 2 hours before subsequent testing.

[0033] Example 2

[0034] A method for preparing an all-solid-state lithium-sulfur composite positive electrode comprises the following steps:

[0035] S1. Add graphene to water and stir and disperse for 0.5 h to obtain solution A; add sodium thiosulfate (Na2S2O3·5H2O) to solution A and stir for 1 h, then slowly add hydrochloric acid (HCl) dropwise and stir for 6 h to obtain solution B (the molar ratio of Na2S2O3·5H2O to HCl is 1:2, and the molar ratio of the conductive agent to Na2S2O3·5H2O is 1:2);

[0036] S2. After filtering and washing solution B six times, drying at 55°C for 12 hours to obtain powder A;

[0037] S3, 60% powder A and 40% electrolyte Li 10 GeP2S 12 , with a ball-to-material ratio of 50:1 and a rotation speed of 600 rpm / min, the mixed ball mill was used for 10 h to obtain powder B;

[0038] S4. Powder B was mixed with 10% binder PVDF (polyvinylidene fluoride) and ground manually for 5 minutes to obtain a composite positive electrode.

[0039] Example 3

[0040] A method for preparing an all-solid-state lithium-sulfur composite positive electrode comprises the following steps:

[0041] S1. Graphene and carbon nanotubes in a mass ratio of 1:1 were added to water and stirred and dispersed for 0.5 h to obtain solution A; sodium thiosulfate (Na2S2O3·5H2O) was added to solution A and stirred for 1 h, and then hydrochloric acid (HCl) was slowly added dropwise and stirred for 6 h to obtain solution B (the molar ratio of Na2S2O3·5H2O to HCl was 1:2, and the molar ratio of the conductive agent to Na2S2O3·5H2O was 1:1);

[0042] S2. After filtering and washing solution B six times, drying at 55°C for 12 hours to obtain powder A;

[0043] S3, 50% powder A and 50% electrolyte Li 10 GeP2S 12 , with a ball-to-material ratio of 40:1 and a rotation speed of 600 rpm / min, the mixed powder was ball-milled for 12 h to obtain powder B;

[0044] S4. Powder B was mixed with 1% binder PTFE and ground manually for 5 minutes to obtain a composite positive electrode.

[0045] Example 4

[0046] A method for preparing an all-solid-state lithium-sulfur composite positive electrode comprises the following steps:

[0047] S1. Add conductive carbon black and acetylene black in a mass ratio of 1:3 into water and stir and disperse for 0.5 h to obtain solution A; add sodium thiosulfate (Na2S2O3·5H2O) into solution A and stir for 1 h, then slowly add hydrochloric acid (HCl) dropwise and stir for 10 h to obtain solution B (the molar ratio of Na2S2O3·5H2O to HCl is 1:2, and the molar ratio of the conductive agent to Na2S2O3·5H2O is 1:2);

[0048] S2. After filtering and washing solution B six times, drying at 50°C for 24 hours to obtain powder A;

[0049] S3, 60% powder A and 40% electrolyte Li3PS4 were mixed at a ball-to-material ratio of 40:1 and a rotation speed of 600 rpm / min for 15 h to obtain powder B;

[0050] S4. Powder B was mixed with 5% binder PTFE and ground manually for 10 minutes to obtain a composite positive electrode.

[0051] Example 5

[0052] A method for preparing an all-solid-state lithium-sulfur composite positive electrode comprises the following steps:

[0053] S1. Add conductive carbon black and acetylene black in a mass ratio of 1:2 into water and stir and disperse for 0.5 h to obtain solution A; add sodium thiosulfate (Na2S2O3·5H2O) into solution A and stir for 1 h, then slowly add hydrochloric acid (HCl) dropwise and stir for 6 h to obtain solution B (the molar ratio of Na2S2O3·5H2O to HCl is 1:2, and the molar ratio of the conductive agent to Na2S2O3·5H2O is 1:2);

[0054] S2. After filtering and washing solution B six times, drying at 50°C for 24 hours to obtain powder A;

[0055] S3, 50% powder A and 50% electrolyte Li3PS4 were mixed at a ball-to-material ratio of 40:1 and a rotation speed of 600 rpm / min for 10 h to obtain powder B;

[0056] S4. Powder B was mixed with 1% binder PTFE and ground manually for 10 minutes to obtain a composite positive electrode.

[0057] Example 6

[0058] A method for preparing an all-solid-state lithium-sulfur composite positive electrode comprises the following steps:

[0059] S1. Add carbon nanotubes to water and stir and disperse for 0.5 h to obtain solution A; add sodium thiosulfate (Na2S2O3·5H2O) to solution A and stir for 1 h, then slowly add hydrochloric acid (HCl) dropwise and stir for 10 h to obtain solution B (the molar ratio of Na2S2O3·5H2O to HCl is 1:2, and the molar ratio of the conductive agent to Na2S2O3·5H2O is 1:2);

[0060] S2. After filtering and washing solution B six times, drying at 50°C for 24 hours to obtain powder A;

[0061] S3. Mix 40% powder A and 60% electrolyte Li6PS5Cl at a ball-to-material ratio of 40:1 and ball mill at a speed of 600 rpm / min for 12 h to obtain powder B.

[0062] S4. Powder B was mixed with 5% binder PTFE and ground manually for 10 minutes to obtain a composite positive electrode.

[0063] Parameters such as stirring speed and time, ball milling speed and time, drying temperature and time, and grinding time can be adjusted by those skilled in the art based on actual experience, and other embodiments resulting from adjusting the above parameters will not be described in detail.

[0064] Comparative experiment:

[0065] Comparative Example 1: To prepare the positive electrode material, sulfur powder and acetylene black in a mass ratio of 1:1 were manually ground for 30 minutes, then heated to 155°C in a tube furnace at a heating rate of 5°C / min and maintained for 10 hours to obtain a molten S / C material; the S / C material and LGPS were mixed in a mass ratio of 40:60 and manually ground for 30 minutes to obtain a composite positive electrode material.

[0066] The all-solid-state lithium-sulfur battery containing the composite positive electrode prepared in Example 1 and Comparative Example 1 was subjected to charge and discharge tests at 0.2C. The results are as follows: Figure 1 As shown in Figure 1, the new composite cathode of Example 1 exhibits a higher discharge specific capacity and a more optimistic capacity retention rate. This shows that for all-solid-state lithium-sulfur battery cathodes, the addition of binders and small molecule sulfur can optimize battery electrochemical performance, increase discharge specific capacity, and slow down capacity decay.

[0067] Those skilled in the art will appreciate that the embodiments described herein are intended to help readers understand the principles of the present invention, and it should be understood that the scope of protection of the present invention is not limited to such specific descriptions and embodiments. Those skilled in the art can make various other specific variations and combinations based on the technical teachings disclosed in the present invention without departing from the essence of the present invention, and such variations and combinations are still within the scope of protection of the present invention.

Claims

1. An all-solid-state lithium-sulfur battery composite positive electrode, characterized in that: The active material sulfur exists in the form of small molecules and is evenly dispersed with the conductive agent and contains a binder that enhances the contact between the particles.

2. A method for preparing an all-solid-state lithium-sulfur battery composite positive electrode, used to prepare the all-solid-state lithium-sulfur battery composite positive electrode according to claim 1, characterized in that: The following steps are involved: S1. Add a conductive agent into water and stir to disperse to obtain solution A; add Na2S2O3·5H2O into solution A and stir, then slowly drop hydrochloric acid and stir to obtain solution B; in solution B, the molar ratio of Na2S2O3·5H2O to hydrochloric acid is 1:2, and the molar ratio of the conductive agent to Na2S2O3·5H2O is 1:1-10; S2, filtering and washing solution B, and then drying to obtain powder A; S3, mixing powder A with electrolyte and ball milling to obtain powder B; S4. Mix powder B and a binder and grind them manually to obtain a composite positive electrode.

3. The method for preparing a composite positive electrode according to claim 2, characterized in that: The conductive agent described in S1 is one or more of graphene, carbon nanotubes, conductive carbon black, acetylene black and Ketjen black.

4. The method for preparing a composite positive electrode according to claim 2, characterized in that: The three stirring times in S1 are 0.5-2h, 1-2h and 6-12h respectively.

5. The method for preparing a composite positive electrode according to claim 2, characterized in that: In S2, suction filtration and cleaning need to be performed 3-10 times, the drying temperature is (50±5)°C, and the drying time is 6-36h.

6. The method for preparing a composite positive electrode according to claim 2, characterized in that: The electrolyte in S3 is Li7P3S 11 、Li3PS4、Li 10 GeP2S 12 , Li6PS5Cl; the amount of electrolyte added is 40%-60% of powder B.

7. The method for preparing a composite positive electrode according to claim 2, characterized in that: In the above S3, the ball-to-material ratio of the mixed ball milling is 50:1-30, the ball milling speed is 200-600 rpm / min, and the ball milling time is 1-24 h.

8. The method for preparing a composite positive electrode according to claim 2, characterized in that: The binder in S4 is polytetrafluoroethylene or polyvinylidene fluoride, and the added ratio of the binder is 1%-20% of the composite positive electrode.

9. The method for preparing a composite positive electrode according to claim 2, characterized in that: The manual grinding time in S4 was 5-15mins.

10. The method for preparing a composite positive electrode according to claim 2, characterized in that: Both S3 and S4 were operated under high-purity argon atmosphere.

Citation Information

Patent Citations

  • A method for preparing sulfur composite cathode material and an all-solid-state lithium-sulfur battery

    CN111799459B

  • LiNbO3 modified composite sulfur solid-state positive electrode material, preparation method thereof and all-solid-state lithium-sulfur battery

    CN118867243A

  • Anode active material, preparation method of anode active material, high-performance anode slurry containing anode active material, and all-solid-state lithium ion battery

    CN106784798A

  • Lithium-sulfur battery composite positive electrode material, preparation method thereof and lithium-sulfur battery

    CN108258204A

  • Composite positive electrode material and preparation method of all-solid-state lithium-sulfur battery

    CN114744194A

Cited By

  • Sulfide solid electrolyte based on gradient hot pressing reaction and preparation method thereof

    CN120841460A

  • A sulfide solid-state electrolyte based on gradient hot-pressing reaction and a preparation method thereof

    CN120841460B